Relationship of Verbal Violent Behavior with Student Learning Achievement - Tina Shinta Parulian Siahaan; Febri Christian Trisna Putra; Susanti Niman (Bulletin of Counseling and Psychotherapy, 2022)
The child is the asset and successor of the ideals of the nation's struggle for the future. Children are entitled to service to develop the ability, and social life, by following per under the culture, and personality of the nation, to become good, and useful citizens. Children are entitled to maintenance and protection, while in the womb or after birth, and children are entitled to protection against the environment that endangers or hinders their growth and development. Child abuse comes in many forms. This study to find out the relationship between verbal violence and student’s learning achievement. We used descriptive quantitative correlation, cross-sectional, for instruments we used questionnaires for verbal violence. Data analysed was a bivariate test that used the chi-square test. Technic sampling used stratified random sampling with lottery technique based on student ID number amount 225 people. There is a significant relationship between verbal abuse and student learning achievement.